“Nature Gives and Nature Takes” - Stopek, Olivia Margareta (2021)
Water and the management of it holds a great complexity. We live in a time where adaptation measures often are based on risk calculations made by experts and bureaucrats where they try to measure future dangers of global climate change. This thesis shifts focus from the global crisis narratives to a grounded and experience-based narrative of a group of Swedish farmers. By examining in depth how farmers in the area of Örebro County, Sweden understand changes to water availability I aim to unravel the farmer’s water epistemology in relation to climate change. What is found is that rather than basing their adaptation measures on expert risk calculations, their adaptations are based on lived experience. The farmers’ water epistemologies consist of their own take on lay- and expert knowledges, and the context they are embedded within. This results in a complex framing of water management moving beyond risk calculations and towards including situated knowledge.